Comparative Analysis of the Gut Microbiota of Mandarin Fish (Siniperca chuatsi) Feeding on Compound Diets and Live Baits - Chen, Xiao; Sun, Chengfei; Dong, Junjian; Li, Wuhui; Tian, Yuanyuan; Hu, Jie; Ye, Xing (Frontiers in Genetics, 2022)
Siniperca chuatsi feeds on live fry throughout their life. The sustainable development of its farming industry has urgently necessitated the development of artificial diets to substitute live baits. It has been demonstrated that gut microbiota assists in feed adaptation and improves the feed conversion rate in fish. Therefore, this study aimed to understand the potential role of intestinal microorganisms in the domestication of S. chuatsi with a compound diet. Accordingly, we performed 16S rRNA sequencing of the gut microbial communities in S. chuatsi groups that were fed a compound diet (including large and small individuals) and live baits. A total of 2471 OTUs were identified, and the large individual group possessed the highest number of unique OTUs. The α-diversity index of the gut microbiota in groups that were fed a compound diet was significantly higher (P < 0.05) than that in the live bait group. There were no significant differences in the α-diversity between the large and small individual groups. However, relatively higher numbers of Lactococcus, Klebsiella, and Woeseia were observed in the intestines of the large individual group. Prediction of the metabolic function of the microbiota among these three fish groups by Tax4Fun revealed that most metabolic pathways, such as glycan metabolism and amino acid metabolism, were typically more enriched for the larger individuals. The results indicated that certain taxa mentioned above exist in large individuals and may be closely related to the digestion and absorption of compound diets. The present study provides a basis for understanding the utilization mechanism of artificial feed by S. chuatsi.